Peran Guru sebagai Pilar Utama dalam Pembentukkan Karakter Peserta Didik di Sekolah Menengah Pertama Madani Makassar: The Role of Teachers as the Main Pillar in Shaping the Character of Students at Madani Junior High School Makassar - Sona, Fitri; Rosdiana; Achruh, Andi (CV. Kalimasada Group, 2023)
In character education, students not only learn about theory and practice but students are invited to reach the cognitive aspect of